Airport systems planning, design, and management - De Neufville, Richard, 1939-; Odoni, Amedeo R.; Belobaba, Peter P.; Reynolds, Tom G. (McGraw-Hill's AccessEngineering., 2013)
"This is a premier text by leading technical professionals, known worldwide for their expertise in the planning, design, and management of airports"-Provided by publisher.